Environmental, developmental, and genetic factors controlling root system architecture - Mansoorkhani, F. M.; Seymour, G. B.; Swarup, R.; Moeiniyan Bagheri, H.; Ramsey, R. J. L.; Thompson, Andrew J. (Taylor & Francis, 2014)
A better understanding of the development and architecture of roots is essential to develop strategies to increase crop yield and optimize agricultural land use. Roots control nutrient and water uptake, provide anchoring and mechanical support and can serve as important storage organs. Root growth and development is under tight genetic control and modulated by developmental cues including plant hormones and the environment. This review focuses on root architecture and its diversity and the role of environment, nutrient, and water as well as plant hormones and their interactions in shaping root architecture.
Keywords: Root; Environment; Hormones; Tomato; Arabidopsis; Rice